Bank performance and executive compensation: a managerial discretion perspective - Magnan, Michael L.; St‐Onge, Sylvie (Strategic Management Journal, 1997)
This study investigates how the relationship between bank performance and executive compensation is affected by the degree of an executive’s managerial discretion. Managerial discretion is captured by two industry-specific attributes: a bank’s strategic domain, and its regulatory environment. Executive compensation is found to be more related to bank performance in a context of high managerial discretion than in a context of low managerial discretion. © 1997 by John Wiley & Sons, Ltd.